Very massive binaries in R 136 - Chené, André-Nicolas (2010)
As recent observations have shown, luminous, hydrogen-rich WN5-7h stars (and their somewhat less extreme cousins, O3f/WN6 stars) are the most massive main-sequence stars known. However, not nearly enough very massive stars have been reliably weighed to yield a clear picture of the upper initial-mass function (IMF). We therefore have carried out repeated high-quality spectroscopy of four new O3f/WN6 and WN5-7h binaries in R136 in the LMC with GMOS at Gemini-South, to derive Keplerian orbits for both components, respectively, and thus to directly determine their masses. We also monitored binary candidates and other, previously unsurveyed stars, to increase the number of very massive stars that can be directly weighed.